KOMUNIKASI PEMASARAN DI HOTEL TAMAN SARI SUKABUMI (Studi Deskriptif Mengenai Komunikasi Pemasaran Terpadu Di Hotel Taman Sari Sukabumi) - Mira Renata; Reihan Salsabila (Jurnalika : Jurnal Ilmu Komunikasi, 2024)
One of the cities in West Java province that attracts tourists to visit is Sukabumi City. Sukabumi City is known as a city with cold weather and has a number of tours that can be visited such as historical tourism and culinary tourism. Judging from the existing infrastructure, the city has experienced significant development in the tourism sector. This can be seen from the number of hotels, tourism destinations and also restaurants both long established and recently established.   In the hospitality business, competition is unavoidable. To anticipate increasingly fierce competition, the hospitality industry must be able to focus more on quality in several ways such as in the use of technology that is efficient, productive, and able to guarantee the superior quality of its products. In addition, hotel marketing can also carry out strategies that exist in marketing communications. Things that need to be considered in marketing communications include market segmentation, market positioning, market entry strategies, timing strategies, and marketing mix strategies. There are several elements in the marketing mix strategy, namely product, place, price, and promotion. Where these promotional activities can be carried out through integrated marketing communication.